INTERFERENSI DALAM CERPEN DI LAMPUNG POST - Ratih Rahayu (Balai Bahasa Provinsi Riau, 2016)
This study attempts to observe the interferences that occur in short stories published in Lampung Post 2010. Various factors that cause interferences in the short stories would be the problems discussed in this study. The use of Indonesian in the short stories fulfilled with the interferences of English and the local languages (Java, Lampung, and Palembang). Interferences occur at the level of morphological, lexical and syntactic. Based on the data, it can be concluded that the interferences are caused by several factors, including bilingualism of authors of the short stories, avoidance of using same words over and over, prestige, lack of fidelity to the language. In addition to, the elements of English and the local languages used are shorter than the elements of Indonesian language and there is no equivalent words in Indonesian.